USING DIRECTED READING THINKING ACTIVITY (DRTA) TECHNIQUE TO IMPROVE STUDENTS’ READING COMPERENSION AT SMP NEGERI 7 KOTA TERNATE - Rusli, Rosmina; Ali, Silvani Umar; Firmansyah, Firmansyah (FKIP Universitas Khairun, 2023)
The purpose of this research is to find out how to using Directed Reading Thinking Activity Technique to Improve Students Reading Comprehension through reading text. This researcher used quantitative methods. The sample consisted of 25 students in class VIII-C SMP Negeri 7 Kota Ternate. The researcher collected data from the pretest and posttest. Pretest data collecting used multiple-choice test in the form of teaching reading through reading text. The data was then analyze based on the aim that the research result could improve students’ comprehension at SMP Negeri 7 Kota Ternate. The result of this research show that the posttest score results were higher than the pretest. The students‟ average pretest score was 1.012 while the posttest average score was 1.718. The t-statistic value of 10,39 was higher than the t-critical value of 1.711 at the significance level (0,05) and the degree of freedom of 24 using one tailed test. It was found that using Directed Reading Thinking Activity learning can improve reading comprehension. Students have a positive response to learning directed reading thinking activity as the method for improving students’ ability to read. It can be seen that there is a significance difference between the pre-test and post-test results.